Mental Health and Its Sociodemographic Determinants among High School Students: A Cross-Sectional Survey in Qazvin City of Iran - Mehran Alijanzadeh (Wolters Kluwer Medknow Publications, 2019)
Introduction: Adolescence is one of the most important stages of human life, and there is a lot of evidence in the literature that psychiatric disorders can be transmitted through adolescence social interactions in high school. The present study aimed to assess mental health and its sociodemographic determinants among high school students in Iran. Methods: In this cross-sectional study, 600 female high school students from Qazvin were selected using cluster sampling. The 28-item General Health Questionnaire was administrated to collect data. t-tests, analysis of variance, and Pearson's correlation analysis were applied to analyze the data. Results: Mental disorders were found in 60% of the students with 3.3% suffered from severe disorders. The participants' mean score of mental health was 29.31 ± 14.63. Somatic symptoms, anxiety, social dysfunction, and depression were presented in 36%, 49.7%, 50%, and 41.3% of the students, respectively. Students' mental health was significantly related with their father's education and household income. However, students' season of birth, school grade, body mass index, grade point average, mother's education, and father's occupation were not significantly related with their mental health. Conclusion: Poor mental health was found to be highly frequent among female students. Low income and father's low education level were identified as the risk factors of poor mental health among female students in Qazvin.